2014
DOI: 10.1017/s0033291714002463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cannabis use disorders: a systematic review of screening and diagnostic instruments

Abstract: Current instruments available for assessing cannabis use disorders need to be further improved. A standard cannabis unit should be studied and existing instruments should be adapted to this standard unit in order to improve cannabis use assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 59 publications
0
28
0
3
Order By: Relevance
“…[44][45][46] Study retention (87%) was also comparable to previous cessation studies for addiction. 44,[47][48][49][50] Number of pills taken (69%) or adherence rate to study medication was moderate compared to previous pharmacological clinical trials. 45,46,51 Of note, 33% of the progesterone group at week 2 had low progesterone blood levels suggesting missing pills.…”
Section: Discussionmentioning
confidence: 70%
“…[44][45][46] Study retention (87%) was also comparable to previous cessation studies for addiction. 44,[47][48][49][50] Number of pills taken (69%) or adherence rate to study medication was moderate compared to previous pharmacological clinical trials. 45,46,51 Of note, 33% of the progesterone group at week 2 had low progesterone blood levels suggesting missing pills.…”
Section: Discussionmentioning
confidence: 70%
“…The lack of consensus reflects the variety of measures that are used, a shortage of longitudinal studies across a range of user profiles to assess problematic outcomes, and the lack of a standardized unit to represent dose or consumption amount, as well as subjective differences in defining one's "problematic" use. 24,25 Future work * Bonferroni correction applied, all estimates have been adjusted using bootstrap weights.…”
Section: Discussionmentioning
confidence: 99%
“…Annaheim [4] recently published a review of 44 instruments designed to assess cannabis-related problems and concluded that the CAST, CUDIT-R, and CUPIT are the most appropriate inventories for screening cannabis-related problems. Similarly, López-Pelayo and colleagues [5] conducted a meta-analytic review that identified 25 instruments to assess cannabis use and cannabis-related problems. They also identified the CAST and CUDIT as two of the highest performing inventories for assessing cannabis-related problems.…”
Section: Introductionmentioning
confidence: 99%